Using Discord to Facilitate Students in Teaching Learning Process during COVID-19 Outbreak - Ardiyansah, Tri Yuli; Batubara, Riska Widiyanita; Auliya, Prativi Khilyatul (Universitas Muhammadiyah Gresik, 2021)
During the COVID-19 outbreak declared by WHO in the end of 2019, classroom activity has been changed into online learning. University has become the institution that is capable of performing online learning for teaching-learning process. In University of Muhammadiyah Gresik, online learning has been performed by its official online learning platform called SPADA UMG. However, students sometimes experience technical issues in using the platform. Therefore, the university allows lecturers to use other kinds of online platforms during the situation of COVID-19 outbreak to make the teaching-learning process more effective. One of the platforms used in online process is Discord. This research focused on analyzing online learning activity by using â€œDiscordâ€ application to facilitate students in online learning process. The writer applied qualitative research design and used questionnaire and interview techniques. The result showed the advantages of using Discord in online learning process provided students with meaningful learning experience. Students were satisfied with the use of Discord in online learning process. It was described into 6 indicators; (1) contents or features, (2) interface, (3) feedback & interaction, (4) studentsâ€™ performance, (5) communication process, and (6) interactivity. In the other hand, few students also reported disadvantages in using Discord concerning the unstable internet connection and low-end device capability